A RESPONSES OF UNDERGRADUATE STUDENTS TOWARD IMPLEMENTATION OF MBKM CURRICULUM OUTSIDE-CAMPUS - Dwirahayu, Gelar; Sobiruddin, Dindin; Satriawati, Gusni; Khairunnisa (MaPan : Jurnal Matematika dan Pembelajaran, 2025)
The Ministry of Higher Education's Regulation No. 3, 2020, issued the MBKM curriculum as a foundation for learning development at the University. Since 2021, the mathematics education study program at UIN Syarif Hidayatullah Jakarta has been carrying out off-campus activities to support the MKBM curriculum. After 4 years of MBKM activities, the study program needs to survey to determine the effectiveness and usefulness of implementing the MBKM program. The purpose of this study is to describe the MBKM program and to find out the undergraduate students’ responses related to this. The research method is qualitative research with a survey method. The population was 288 undergraduate students in the mathematics study program, and the sample was 150. The instrument is a questionnaire to determine the effectiveness of the socialization of the MBKM program, the extent of understanding and perception of the MBKM curriculum, and its implementation. The results showed: 1) 27% of undergraduate students got information from the study program, 2) 78% of undergraduate students understood about the MBKM curriculum, and 3) more than 50% of undergraduate students agreed that outside-campus activities can improve teaching skills, mathematical content, and technology mastery. It was concluded that MBKM activities outside-campus positively impacted undergraduate students and need to continue. Recommendation: study programs need to conduct intense socialization about MBKM, and continue the outside-campus program, to train undergraduate students' pedagogical skills, content knowledge, and technology skills. Abstrak: Permen Ristek Dikti nomor 3 tahun 2020 menerbitkan kurikulum MBKM sebagai landasan pengembangan pembelajaran di Perguruan Tinggi. Program studi pendidikan matematika UIN Syarif Hidayatullah Jakarta telah melaksanakan kegiatan di luar kampus sejak tahun 2021 untuk mendukung kurikulum MKBM. Setelah 4 tahun kegiatan MBKM berlangsung, program studi perlu melakukan survei untuk mengetahui efektifitas dan kebermanfaatan program MBKM. Tujuan dari penelitian ini yaitu mendeskripsikan kegiatan pada program MBKM dan mengetahui respon mahasiswa terkait dengan kegiatan MBKM yang telah dilaksanakan. Metode penelitian yang digunakan adalah penelitian kualitatif dengan metode survei. Populasinya sebanyak 288 mahasiswa aktif pada Program Studi Pendidikan Matematika,  sampel penelitian sebanyak 150. Instrumen yang digunakan dalam penelitian ini adalah angket. Angket digunakan untuk mengetahui efektivitas sosialisasi program MBKM, tingkat pemahaman mahasiswa terhadap kurikulum MBKM dan persepsi  terhadap implementasinya. Hasil penelitian menunjukkan bahwa 1) 27% mahasiswa mendapatkan informasi  tentang  kurikulum MBKM dari program studi, 2) 78% mahasiswa memahami tentang kurikulum MBKM, dan 3) lebih dari 50% mahasiswa memahami menyatakan setuju bahwa kegiatan di luar kampus dapat meningkatkan keterampilan mengajar, kemampuan konten matematika, dan meningkatkan penguasaan teknologi. Berdasarkan hasil penelitian disimpulkan  bahwa kegiatan MBKM di luar kampus memberikan dampak positif bagi mahasiswa dan tetap dilaksanakan. Rekomendasi: program studi perlu melakukan sosialisasi tentang MBKM secara intens, dan tetap melanjutkan program MBKM di luar kampus, untuk melatih kemampuan pedagogis, pengetahuan konten matematika, dan kemampuan memanfaatkan teknologi mahasiswa.